Usury (Riba) and the Place of Bank Interest in Islamic Banking and Finance - Zaman, M. Raquibuz (Universiti Utara Malaysia, 2009)
This paper examines the concept of usury or Riba as was understood at the time of the Prophet of Islam and his contemporaries in Mecca and Medina, and what differing interpretations of the term developed in succeeding centuries in Muslim populated countries of the world. It gives a brief summary of the concept of usury in Judaism and Christianity and how this term is equivalent of Riba in Islam. It demonstrates that Riba and interest are not synonymous terms, and that what Islam forbids is usury and not interest. It asserts that, although some interests are usurious, the claim by the contemporary Islamic Banking and Financial institutions, IBFIs, that these institutions are “Islamic” because the term is not used in their transactions, is misleading at best. It ends with the proclamation that true IBFIs are not only feasible, but also are inevitable to serve the needs of the Muslims around the world.